2010
DOI: 10.1038/nrcardio.2010.115
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory mechanisms in vascular calcification

Abstract: In the past decade, the prevalence, significance, and regulatory mechanisms of vascular calcification have gained increasing recognition. Over a century ago, pathologists recognized atherosclerotic calcification as a form of extraskeletal ossification. Recent studies are identifying the mechanisms of this remarkable process as a recapitulation of embryonic endochondral ossification through phenotypic plasticity of vascular cells that function as adult mesenchymal stem cells. These embryonic developmental progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
428
1
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 501 publications
(444 citation statements)
references
References 133 publications
(129 reference statements)
6
428
1
9
Order By: Relevance
“…Consequently, no effective therapies are available. Increasing body of recent evidence has challenged the traditional consideration of vascular calcification as a passive aging-related process and points to specific mechanisms of its regulation depending on diseaserelated environmental cues [32,33]. A role of circulating calcifying cells in this process is emerging [34].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, no effective therapies are available. Increasing body of recent evidence has challenged the traditional consideration of vascular calcification as a passive aging-related process and points to specific mechanisms of its regulation depending on diseaserelated environmental cues [32,33]. A role of circulating calcifying cells in this process is emerging [34].…”
Section: Discussionmentioning
confidence: 99%
“…Mineralization of the vasculature is associated with an excess risk of cardiovascular events due to an increase in arterial stiffness and pulse wave velocity (32,33). Different factors including a mineral imbalance promote vascular calcification, whereas endogenous local or circulating calcification inhibitors suppress vascular calcification by blocking the deposition of minerals in the vascular wall or by the transformation of vascular smooth muscle cells (VSMC) to osteochondrogenic cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…8 Although initially considered a passive, uncontrollable process, recent evidence supports AIC as an actively regulated process with similarities to bone development, including the appearance of calcified cartilage-and bone-like structures within le-sions. [9][10][11] Lineage tracing studies in mouse models have shown that vascular smooth muscle cells (SMCs) can transdifferentiate into osteochondrogenic cells, 12,13 implicating these cells as important mediators of AIC. However, the mechanisms by which SMCs transdifferentiate and contribute to plaque mineralization are not well understood.…”
Section: Introductionmentioning
confidence: 99%